The Phases of the Postwar Evolution of Capitalism: the Transition from the Current Crisis into a New Worldwide Developmental Trajectory - Vlados, Charis (Perspectives on global development and technology, 2019)
Abstract This article focuses on the evolutionary dynamics of the world economy after the Second World War to current day by reviewing the subject in evolutionary and holistic terms. In particular, its purpose is to examine the structuring of the current crisis and the prospects for overcoming it by advancing toward a new developmental phase, a new sustainable model of global development. We articulate our approach precisely at the link between the interconnection and the dialectic interdependence of the central structural components of global dynamics. In this direction, we introduce, propose, and utilize a three-sided structural analysis of global dynamics, a triptych. In particular, we claim that the changes in the global system are imprinted and can be studied at three co-located and dialectically interwoven central structural levels: at the level of current international regimes, at the level of central models of development and crisis, and at the level of the dominant types of business innovation. As a whole and on every level, the structural changes define and form in the background the evolutionary dynamics of the world economy, and thus by extension prescribe the conditions for the global system to construct the trajectory to exit from its current crisis.